Biomechanical evaluation of different posterior fixation techniques for treating thoracolumbar burst fractures of osteoporosis old patients: a finite element analysis - Zhang, Guodong; Du, Yukun; Jiang, Guangzong; Kong, Weiqing; Li, Jianyi; Zhu, Zhongjiao; Xi, Yongming (Frontiers in Bioengineering and Biotechnology, 2023)
Objective To investigate the biomechanical characteristics of different posterior fixation techniques in treatment of osteoporotic burst thoracolumbar fractures by finite element analysis.The Dicom format images of T10-L5 segments were obtained from CT scanning of a volunteer, and transferred to the Geomagic Studio software, which was used to build digital models. L1 osteoporotic burst fracture and different posterior fixation techniques were simulated by SolidWorks software. The data of ROM, the maximum displacement of fixed segment, ROM of fractured L1 vertebrae, the stress on the screws and rods as well as on fractured L1 vertebrae under different movement conditions were collected and analysed by finite element analysis.Among the four groups, the largest ROM of fixed segment, the maximum displacement of fixed segment and ROM of fractured vertebrae occurred in CBT, and the corresponding data was 1.3°, 2.57mm and 1.37°, respectively. While the smallest ROM of fixed segment, the maximum displacement of fixed segment and ROM of fractured vertebrae was found in LSPS, and the corresponding data was 0.92°, 2.46mm and 0.89°, respectively. The largest stress of screws was 390.97Mpa, appeared in CBT, and the largest stress of rods was 84.68MPa, appeared in LSPS. The stress concentrated at the junction area between the root screws and rods. The maximum stress on fractured vertebrae was 93.25MPa, appeared in CBT and the minimum stress was 56.68MPa, appeared in CAPS. And the stress of fractured vertebrae concentrated in the middle and posterior column of the fixed segment, especially in the posterior edge of the superior endplate.In this study, long-segment posterior fixation (LSPF) provided with the greatest stability of fixed segment after fixation, while cortical bone screw fixation (CBT) provided with the smallest stability. Cement-augmented pedicle screw-rod fixation (CAPS) and combined using cortical bone screw and pedicle screw fixation (CBT-PS) provided with the moderate stability. CBT-PS exhibited superiority in resistance of rotational torsion for using multiple connecting rods. CAPS and CBT-PS maybe biomechanically superior options for the surgical treatment of burst TL fractures in osteoporotic patients.